2017
DOI: 10.1103/physrevb.96.245119
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning Z2 quantum spin liquids with quasiparticle statistics

Abstract: After decades of progress and effort, obtaining a phase diagram for a strongly-correlated topological system still remains a challenge. Although in principle one could turn to Wilson loops and long-range entanglement, evaluating these non-local observables at many points in phase space can be prohibitively costly. With growing excitement over topological quantum computation comes the need for an efficient approach for obtaining topological phase diagrams. Here we turn to machine learning using quantum loop top… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 59 publications
(103 reference statements)
1
71
0
Order By: Relevance
“…Therefore, artificial-neuralnetwork quantum states are not necessarily needed to use ML for topological states. In the same spirit, Zhang et al showed that the phase boundary between the topological and trivial phases for the Z 2 quantum spin liquid can be identified by feed-forward neural networks by defining quantum loop topography sensitive to quasiparticle statistics [503].…”
Section: Quantum Phase Transition In Topological Insulator Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, artificial-neuralnetwork quantum states are not necessarily needed to use ML for topological states. In the same spirit, Zhang et al showed that the phase boundary between the topological and trivial phases for the Z 2 quantum spin liquid can be identified by feed-forward neural networks by defining quantum loop topography sensitive to quasiparticle statistics [503].…”
Section: Quantum Phase Transition In Topological Insulator Modelsmentioning
confidence: 99%
“…The success of ML techniques in topological phase models aroused interest in experimentally fabricated systems, which in turn gave rise to the study of topological band insulators models [503], e.g., the Su-Schrieffer-Heeger model. Thus, using the Hamiltonian in the momentum space as an input of convolutional neuralnetworks, Zhang et al found a model for the topological invariant of general one-dimensional models, i.e., the winding number [503]. Although the winding number for a one-dimensional Hamiltonian k h ih x y , in [503], the authors found an equivalent neural-network-based expression for more general Hamiltonians.…”
Section: Quantum Phase Transition In Topological Insulator Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, this topic has attracted much attention from physicists because of the strong performance of detecting, predicting and uncovering various phases of matter in quantum many-body systems [2][3][4][5][6][7][8][9][10][11][12][13]. Neural network based models play an irreplacable role in this field because they're able to not only learn generate phases or states of matter that are previously known [4,5,7,12] or uncovering phase transitions [2,3,6], but predict out-ofequilibrium phases of matter that have not been known yet [13]. Both Feed-Forward Neural Network (FFNN) and Convolutional Neural Network (CNN) have been ex-ploited to learn and discover the hidden pattern of phase transition in Ising-type lattice structures [7].…”
Section: Introductionmentioning
confidence: 99%